Cover Feature: Monomeric Magnesium Catalyzed Alkene and Alkyne Hydroboration (Chem. Eur. J. 56/2022). Issue 56 (26th September 2022) - Kumar, Rohit; Dutta, Sayan; Sharma, Vishal; Singh, Praval P.; Gonnade, Rajesh G.; Koley, Debasis; Sen, Sakya S.
Abstract : From traditional to sustainable : Catalysts with platinum‐group metals are well‐established in the field of hydroboration of C−C multiple bonds. However, the current mantra in catalysis is to employ "cheap metals for noble tasks". In this regard, we have developed a bis(phosphino)carbazolido magnesium‐methyl complex as a catalyst for the hydroboration of alkenes, alkynes, and biologically essential terpenes by using pinacolborane (HBpin) as a hydride donor. More information can be found in the Research Article by R. G. Gonnade, D. Koley, S. S. Sen and co‐workers (DOI: 10.1002/chem.202201896 ).